Antidiabetic and Antihyperlipidemic Effects of Methanolic Extract of Leaves of Spondias mombin in Streptozotocin-Induced Diabetic Rats - Gobinath, Ramachawolran; Parasuraman, Subramani; Sreeramanan, Subramaniam; Enugutti, Balaji; Chinni, Suresh V. (Frontiers in Physiology, 2022)
Objective: Spondias mombin is a plant that reported to have anticonvulsant, antimicrobial, antioxidant, antiulcer, antiasthmatic and wound healing activities. Diabetes dyslipidemic effect of Spondias mombin leaves is not clear. Hence, current study planned to evaluate the antidiabetic and antihyperlipidemic effects of methanolic extract of leaves of Spondias mombin (MESM) in streptozotocin (STZ) induced diabetic rats. Methods: Phytochemicals were determined by standard method and antioxidant activity was determined by DPPH free radical scavenging and FRAP assay. Diabetes was induced by injecting a single dose of STZ (55 mg/kg) into female Sprague Dawley rats. After three days of induction of diabetes, the diabetic animals were treated for 28 days with MESM (125, 250 and 500 mg/kg) and glibenclamide (20 mg/kg) orally. The body weight of rats and blood glucose levels were monitored at regular intervals during the experiment. At the end of study, blood sample was collected from all the animals and subjected to biochemical, lipid profile and they were sacrificed and their organs such as pancreas, liver and kidney were used for histopathological analysis. Results: Quantitative analysis of MESM showed the presence of anthraquinone, tannins, saponins, steroid, phenols, flavonoids, alkaloids and reducing sugars. Reduction in body weight and elevated blood glucose were observed in diabetic rats. Treatment with MESM in a concentration of 125, 250 and 500 mg/kg significantly reversed the elevated levels of blood glucose, biochemical parameters and lipid profile. Conclusion: MESM exhibited a significant antidiabetic and antihyperlipidemic activities against STZ-induced diabetes in rats.